Development of Fishery Marketplace Applications Using Prototype Methods - Bao Sumantoro, Yeremia Joen; Rohmani, Asih; Budiman, Fikri; Sugiarto, Edi (Devotion : Journal of Research and Community Service, 2023)
Fish farming is an activity of raising fish or developing fish in a controlled environment. However, if you look at the statistical data, the fish consumption level of Kendal Regency residents is still low, namely 24 kg/cap/year, far below the national fish consumption rate. From the existing problems, fish cultivators, especially those in the border areas of Kendal Regency, mostly sell their fish production outside the area. As a result, the selling price is lower because it is deducted from the transport price. Another problem occurs for cultivators who are just starting a business. Usually they have sufficient capital to build a business, but they do not yet have acquaintances with fish traders who are willing to buy their crops. So they often use social media facilities to offer their crops. Based on the existing problems, it is possible to help solve problems by utilizing information technology. Utilization of a technology in selling fish can help farmers so that sales are more focused and produce good sales, so an application is made that is expected to help overcome existing problems, researchers use the prototype method to find out user needs